Vertical‐cavity surface‐emitting laser with integrated surface grating for high birefringence splitting. Issue 19 (1st September 2019) - Pusch, T.; Debernardi, P.; Lindemann, M.; Erb, F.; Gerhardt, N.C.; Hofmann, M.R.; Michalzik, R.
Abstract : Increasing the birefringence splitting in single‐mode vertical‐cavity surface‐emitting lasers (VCSELs) enables high‐speed polarisation dynamics which can be the basis to overcome the current bandwidth limitations in short‐haul data transmission. The authors observe large birefringence splittings of up to 98 GHz in an oxide‐confined AlGaAs‐based VCSEL with a tailored integrated surface grating. Since surface gratings are routinely used in VCSEL production, there is a great potential of this technique to realise spin‐VCSELs for ultrafast optical communication.